Denervation increases the degradation rate of acetylcholine receptors at end-plates in vivo and in vitro. - Bevan, S (1983)
We have studied the effect of denervation on the degradation of the existing junctional acetylcholine (ACh) receptors at end-plates in rat muscles. ACh receptors were labelled by injecting animals with iodinated alpha-bungarotoxin (I-alpha BT); 1 day later the left hemidiaphragm was denervated. The degradation of bound I-alpha BT in normal and denervated muscles was examined in organ culture, beginning at various times after denervation in vivo. The original, pre-labelled end-plate ACh receptors are degraded more rapidly after denervation. The rate of degradation begins to increase shortly after the nerve is cut and reaches a maximum value at about 9 days of denervation. Muscles denervated only on transfer to organ culture also show an increase in the degradation rate of bound I-alpha BT with increasing time of denervation (time in culture). In normal diaphragm muscles, the initial rate of degradation of functional ACh receptors, after correcting for non-degradative loss of I-alpha BT, is 0.0018 h-1 (t1/2 = 383 h). The maximal rate at denervated end-plates is 0.0073 h-1 (t1/2 = 94 h). For soleus, sternomastoid, plantaris and intercostal innervated muscles the apparent rate of ACh receptor degradation either in vitro or in vivo ranged from 0.0005 h-1 to 0.002 h-1. The rate of loss of bound I-alpha BT in vivo is more rapid at denervated end-plates than at innervated end-plates. For diaphragm muscles, the rates of I-alpha BT degradation measured in organ culture are able to describe the relative rates of loss of I-alpha BT from innervated and denervated muscles in vivo. At short times after labelling, a fraction (10-20%) of the I-alpha BT bound to innervated muscles is degraded more rapidly than the remaining toxin. The possibility that these I-alpha BT binding sites are degraded at the rate characteristic of extrajunctional receptors on denervated muscle fibres is discussed.